PRODUÇÃO DE SENTIDOS NA INFÂNCIA: MEDIAÇÕES NA RECEPÇÃO DA SÉRIE DE ANIMAÇÃO DOUG FUNNIE - Generozo, Amanda Yara (2015)
The present research is intended for bringing a reflection about the reception processes of cultural products by child viewers. The questioning lies in investigating it, making use of the theoretical framework of communicative mediations of culture and full focus on audience, that is, the manner how children aged between 7 and 12 interact with audiovisual stories, especially animated television series, in order to understand, from this perspective, the acquisition and the production of meaning in daily life, taking the interpretation of the cartoon Doug Funnie as basis. As methodology, the study applies literature review combined with a discussion group guided by the theoretical and methodological model of multiple mediation formulated by Guillermo Orozco Gómez, based on the mediation paradigm of Jesús Martín-Barbero. The reception research, carried out in the school environment, verified that media communication has a dialogic nature and implies recognition and projection of the viewer with the fiction universe. Therefore, the production of meaning in what concerns television cartoon is not contained in the audiovisual scenario, but in the social and cultural context in which interlocutors relate with each other and with the media. From this interaction, understanding and development of cultural products emerge, then signaling that the interpretation of the child viewers reveals their particular manner of seeing the world.